PSYCHOLOGICAL FEATURES OF INCREASE OF STRESS RESISTANCE IN ADULTS (Psychology Travelogs, 2023)
To date, it can be noted that modern realities (full-scale war in Ukraine, martial law, threats to life, forced resettlement, occupation of Ukrainian territories, shelling, "Air Alarm" signals, etc.) have caused an increase in the level of stress in the human body, which, accordingly was reflected in the state of their health.The article carries out a theoretical analysis of the phenomenon of "stress", "stress resistance". It is noted that in psychological science there are various scientific approaches to determining their content. Thus, scientists understand "stress" as a strong, unfavorable, negative influence on the human body. "Resilience to stress" is a personality trait that is structural-functional, dynamic and integrative. Scientists have identified the causes of stress in humans and described its impact on the human body.It was determined that in psychological science the term "maturity" is often replaced by the term "adulthood". The concept of "personal maturity" is a characteristic of a person determined by certain requirements and specific manifestations of the components of his life activities. According to scientists, representatives of mature age are people who already have clear ideas about life, a clear position in life, a formed worldview and a system of values.In the course of the research, it was determined that many researchers are studying problematic issues related to increasing the stress resistance of adults through the use of various directions, methods and techniques. Psychologists have proposed areas of work to increase the stress resistance of the individual. Thanks to their competent use, the specialist is able to increase the stress resistance of the individual to various stress factors, which, in turn, will have a positive effect on both the physiological and mental health of the person.The research presents the results of the application of one of the methods, as well as an analysis of the state of stress resistance in men and women.
Keywords: stress; stress resistance; stress factors; personal maturity; mature age; gender